The Equal and the More Equal: Pupils' Experiences of School in Lithuania in the late Soviet Era - Stonkuvienė, Irena (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to reveal the experiences and attitudes of pupils who attended schools in the late Soviet era (1960s-1980s) towards the implementation of egalitarianism policies in the schools of the Lithuanian SSR. The analysis of the qualitative research material focuses on the word "felt" in the phrase "We all felt equal then", i.e., not so much on the fixation of social (in)equality by analysing the indicators of social class or economic status, but on the subjective experience of equality as a manifestation of human dignity.Methods. Following the methodology of oral history, material was collected during 32 in-depth interviews with people who had attended schools in the Lithuanian SSR in the late Soviet era.Results. Several themes emerged from the analysis of the interviews relating to the expression of egalitarianism in the Soviet school: the social class of the pupils; the economic situation of the parents; and the ability of the parents to have the so-called "blat".Conclusions. The study revealed that the implementation of the policy of egalitarianism officially declared by the Communist Party in the education system was subject to several reservations. In Soviet Lithuania, just as in the whole society, there were a lot of manifestations of blat, corruption, and favouritism. These were influenced by the positions held by pupils' parents, belonging to the nomenklatura and/or the ability to establish informal contacts. Pupils from rural schools had fewer opportunities to pursue higher education.